Operational Plan for Scaling Teacher Access to Training and Support for Integrating ICT and Interactive Pedagogy with Virtual Reality in two Indian States: Maharashtra and Telangana - Tara Stafford Ocansey; Radhika Iyengar; Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
Technology has many uses to improve the quality of education. This paper uses Virtual Reality (VR) as a medium to improve teacher's teaching styles. The objective of the paper is to use a reliable technology that can help to improve the teacher training techniques. Instead of relying on traditional teacher training methods, these simulated modules will help the teachers to get a refresher training very close to the schools. The VR platform developed with the support of Ericsson has been piloted in Myanmar based secondary schools before. The Ministry of Education helped to implement VR based teacher training for secondary school teachers in Myanmar. The teachers provided useful feedback and the modules were further revised. The modules focus on teaching styles. How should the classroom be made more inclusive? Is the teacher giving every student a chance to speak-up? What are the ways that the teachers can engage the students in the classroom? Irrespective of the content being taught, some generic principles on teacher training pedagogies could be made an integral part of any teacher training. This study will help to see if the modules will help the teachers in two states in India-Telangana and Maharashtra. VR will be employed in the States' teacher training center in Maharashtra and a DIET in a district in Telangana. The trainers attending the trainings in the two States will be very different, for Telangana it will be the DIET faculty. For Maharashtra, it could be the State level teacher trainers. Therefore, the modalities of how the teacher training is delivered and to whom will be different and thus the modules can also tested in the two States.
Keywords: 330